2022
DOI: 10.3390/ma15051746
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Corrosion Behavior of Strong and Ductile High Mn-Low Cr Steel in Acidic Aqueous Environments

Abstract: To expand the industrial applicability of strong and ductile high Mn-Low Cr steel, a deeper understanding and mechanistic interpretation of long-term corrosion behavior under harsher environmental conditions are needed. From this perspective, the long-term corrosion behaviors of 24Mn3Cr steel under acidic aqueous conditions were examined through a comparison with conventional ferritic steels using the electrochemical measurements (linear polarization resistance and impedance), and immersion test followed by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 23 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…Cr [9][10][11][12][13], as a universally recognized primary corrosion-resistant element, has been the subject of extensive research. Studies have shown that Cr can shift the self-corrosion potential of the steel matrix positively, and when the Cr content is higher, a passive film can form.…”
Section: Introductionmentioning
confidence: 99%
“…Cr [9][10][11][12][13], as a universally recognized primary corrosion-resistant element, has been the subject of extensive research. Studies have shown that Cr can shift the self-corrosion potential of the steel matrix positively, and when the Cr content is higher, a passive film can form.…”
Section: Introductionmentioning
confidence: 99%